Departamento de Odontologia Infantil e Social - Delbem, Alberto Carlos Botazzo; Dossi, Ana Paula; Garbin, Artênio José Isper; Percinoto, Célio; Saliba, Cléa Adas; Santos, Eduardo César Almada; Bertoz, Francisco Antonio; Pessan, Juliano Pelim; Mendonça, Marcos Rogério de; Sundefeld, Maria Lúcia Marçal Mazza; et al. (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação - Robson Frederico Cunha